IoT based water quality monitoring system for aquaponics - Mohd Pu'ad, Muhamad Farhan; Sidek, Khairul Azami; Mel, Maizirwan (Institute of Physics Publishing, 2020)
Most tasks can be done remotely nowadays with the help of the Internet of Things (IoT). IoT can also be applied in the agriculture sector such as aquaponics where water quality is crucial to be kept track at all time to avoid loss of resources. Personnel used for water quality checking on-site is becoming less practical for the technologies available today. Remote monitoring system using IoT is essential for water quality monitoring. However, the lack of attention was given by local farmers for applying it in aquaponics. In this study, an IoT based water quality monitoring system for aquaponics was developed to shift from monitoring water quality on-site to remote monitoring via the Internet. Several open-source software was used in developing the monitoring system. The system covers a web server which is accessible via the Internet for user convenience today. Several tests were carried out on aquaponics in the Malaysian Institute of Sustainable Agriculture (MISA). The result shows that the system can display measurements over time and alert users via the dashboard. Other than that, observation indicates that the reporting system is stable and reliable to be used in an aquaponics system.